The Sino-US Relationship: Case Study of the United States Policy on One China Policy - Xupueng Liu (International Journal of Science and Society, 2019)
Taiwan and China began a conflict when differences in the integrity of the two countries who wanted full sovereignty in one country and China made "one Chinese policy" agreed by the two countries. When the United States established diplomatic relations with Taiwan, China regarded Taiwan as a barrier to ties between the PRC and the United States and violated the "One China Policy" agreement. This research uses the descriptive method, with the concept of Strategic Ambitiousity.